Optimal Control Design of Eco-Friendly Power Generators Using Wind Power - Ahmad Nadhir; Agus Naba (Natural B, Journal of Health and Environmental Sciences, 2012)
Two optimal control methods based on fuzzy inference system (FIS) for maximizing extraction of energy in wind energy conversion system (WECS) is already presented. An MPPTFIS is a first optimal control method using maximum power point tracking approach and fuzzy system. The objective of MPPTFIS is to make zero value change rate of power and rotor speed. A control system will drive an actuator to increasing or decreasing the generator speed depend on the measurement rate of power and rotor speed. An optimal of WECS can be achieved by carried through the rate of power and rotor speed that operating near optimal point. The second optimal control method is proposed by using adaptive neuro fuzzy inference system (ANFIS) to finding model of power curve that will be applied for design of linear control feedback (LCANFIS). The advantage of LCANFIS than MPPTFIS is only one parameter measusrement needed: wind speed. MPPTFIS and LCANFIS could maximize extraction of the wind energy that verified by a power coefficient Cp stay at its maximum almost all the time and an actual power line close to a maximum power extraction (MPE) line reference during simulation process using a same of wind profile.